2018
DOI: 10.3390/min8080327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mineral Resource Potential of Atlantic Ferromanganese Crusts Based on Their Growth History, Microstructure, and Texture

Abstract: Abstract:The decarbonisation of our energy supply is reliant on new technologies that are raw material intensive and will require a significant increase in the production of metals to sustain them. Ferromanganese (FeMn) crusts are seafloor precipitates, enriched in metals such as cobalt and tellurium, both of which have a predicted future demand above current production rates. In this study, we investigate the texture and composition of FeMn crusts on Tropic Seamount, a typical Atlantic guyot off the coast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The sediment used for the plume experiments ( Fig. 2a) was predominantly "muddy sand" (on average 1% gravel, 84% sand and 15% silt/clay) and pelagic in origin 25 . Pterapod shells were clearly visible in the plumes created in the plume experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sediment used for the plume experiments ( Fig. 2a) was predominantly "muddy sand" (on average 1% gravel, 84% sand and 15% silt/clay) and pelagic in origin 25 . Pterapod shells were clearly visible in the plumes created in the plume experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2d) of 3 cm (on average) and up to 16 cm. Typically, the crust has bulk and dry densities of 1950 kg/m 3 and 1740 kg/m 3 , respectively 25 . The crust material Plume observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We combined these techniques in a case study of bacterioplankton growth in the sheath-water of a typical, standalone seamount -Tropic Seamount located in the North-Eastern tropical Atlantic Ocean 24 . Tropic Seamount was selected because it is sufficiently (~3,000 m) tall to retain deep-ocean water yet its summit is deep enough below the ocean surface (~1,000 m) to cause no pronounced surface seamount effect, which would unnecessary complicate the already challenging assessment.…”
mentioning
confidence: 99%
“…Previous studies reported on three processes which gave rise to the Fe-oxyhydroxide deposits (i) The Fe-Si-Mn types that are predominantly formed by diffuse hydrothermal flow [3,12]. (ii) The Fe-Si-Mn types that are precipitated by seawater [31][32][33][34] and (iii) the Fe-Si-Mn types that are formed by mass wasting and corrosion of pre-existing sulfides [2,14]. However, these processes rarely occur in isolation and each may play an essential role in the precipitation of Fe-Mn oxyhydroxides at different stages [35,36].…”
Section: Origin and Formation Process Of Wocan-1 Fe-oxyhydroxidesmentioning
confidence: 99%